Answer:
27 and 60
Explanation:
lets say the first number 'a' and the second number 'b'
1) The question says the sum of two number is 87 which means a + b = 87........given 1
2) we have another given which says one of the number is 6 morethan twice the other which means a = 2b + 6.......... given 2
a + b = 87
2b + 6 + b = 87 (we substitute 'a' with the given 2b + 6)
3b + 6 = 87
3b = 87 - 6
3b = 81
3b = 81
3 3
b = 27 ..... the first number
a = 2b + 6
a = 2 × 27 + 6
a = 54 + 6
a = 60..... the second number
hope u like it ❤️❤️❤️
For any question comment me